Analysis of the Prognostic Significance and Immune Infiltration of the Amino Acid Metabolism-Related Genes in Colon Adenocarcinoma - Wang, Zhenling; Huang, Changzhi; Wu, Jingyu; Zhang, Hongqiang; Shao, Yu; Fu, Zan (Frontiers in Genetics, 2022)
Amino acid metabolization is verified to take part in the progression of cancer. However, genes related to amino acid metabolism have not been identified in colon adenocarcinoma (COAD). A systematic prognostic model of COAD becomes a pressing need. RIMKLB, ASPG, TH, MTAP, AZIN2, PSMB2, HDC, ACMSD, and PSMA8 were identified to construct a risk model. Kaplan-Meier (K-M) analyses demonstrated that the high-risk group achieved a poor prognosis. Area under the respective ROC (AUC) values indicated the robustness of the model. Cox regression reduced clinically characters to age, T, stage, and risk score. A nomogram was shaped to correspond with achieved clinicopathology features. A higher tumor mutation burden was observed in the high-risk group. However, the low-risk group had a stronger immune infiltration. Seven molecular subtypes were found by consensus cluster. 22 hub genes were identified related to ESTIMATE score using WGCNA. In brief, our research constructed a stable prognostic model related to amino acid metabolism in COAD, revealing its connection to the immune microenvironment. The model guided the outcome of COAD and the direction of immunotherapy.